Silica/Methylaluminoxane/(n‐BuCp)2ZrCl2: Effect of Silica Dehydroxylation Temperature on HDPE Morphology. Issue 1 (February 2016) - Bashir, Muhammad Ahsan; Monteil, Vincent; Boisson, Christophe; McKenna, Timothy F.L.
Summary: Morphology and particle size distribution (PSD) of high density polyethylene (HDPE) produced in slurry and gas phase ethylene homopolymerisations have been analysed in connection with the catalytic activity of silica supported (n‐BuCp)2 ZrCl2 /Methylaluminoxane (MAO) catalysts. It has been shown that the silica dehydroxylation temperature affects the catalytic activity of these silica supported catalysts in ethylene homopolymerisation which, in turn, affects the polymer morphology and PSD. Thick fibrous HDPE is observed in all the polymer samples produced via slurry phase process, whereas, the gas phase process HDPE samples did not show such fibrous structures. PSD of the polymers replicate the PSD of silica support and shifts towards larger particle size with increase in productivity which is related to silica dehydroxylation temperature.